Flower phenology and artificial pollination timing in two parental Excelsa coffee (Coffea liberica var. dewevrei) - GILMAN AIMAN NAJIB; MUSTOFA MUSTOFA; YUDITHIA MAXISELLY; SANTI ROSNIAWATY (Smujo International, 2026)
Abstract. Najib GA, Mustofa, Maxiselly Y, Rosniawaty S. 2026. Flower phenology and artificial pollination timing in two parental Excelsa coffee (Coffea liberica var. dewevrei). Asian J Agric 10 (1): g100142. https://doi.org/10.13057/asianjagric/ g100142. Excelsa coffee is a cross-pollinating coffee variety whose reproductive success depends on synchronization between flower phenology and pollination timing. However, information on flower development and artificial pollination timing in Excelsa coffee remains limited. This exploratory descriptive field study aimed to determine (i) the duration required for flower buds to reach the phenologically suitable stage for pollination and (ii) the artificial pollination timing associated with more rapid progression toward early fruit development under observed conditions. Field observations were conducted at Agricultural Assembly and Modernization Agency: Industrial and Refreshing Plant, Indonesia, using two six-year-old parental of Excelsa coffee plants (n=2) that pollinated multiple times and gained 12 successful pollination flowers as the samples. Flower development was monitored from inflorescence emergence (stage 51) to early fruit development (stage 71) following the BBCH scale. Parameters observed included flower bud number, flower bud length, duration to the phenologically suitable stage, and time from pollination to initial fruit development. Artificial pollination was performed at 05:00, 06:00, 07:00, and 08:00 AM, with three pollinated flowers per treatment. Data were analyzed descriptively using means, standard deviations, and population variance, and thermal accumulation was assessed using Growing Degree Days (GDD). Results showed that flower buds required approximately 25-30 days to reach the phenologically suitable stage for pollination. 70% of buds reached BBCH stage 58 on day 25, with a mean bud length of 8.03 mm, while first flowering (BBCH 60) occurred around day 30. Flower bud length exhibited greater variability during early development and became more uniform toward later stages. Following artificial pollination, all treatments reached BBCH stage 70 by day 7; however, under the observed conditions, pollination at 08:00 AM was associated with faster progression to BBCH stage 71, with 66% of samples reaching this stage by day 13. These findings provide baseline phenological information and indicate a narrow temporal window suitable for artificial pollination in Excelsa coffee under the observed conditions.